MANAJEMEN KOLABORASI DALAM PENGELOLAAN LINGKUNGAN UNTUK MEWUJUDKAN PABRIK SEMEN RAMAH LINGKUNGAN - Wildan Rayadi (Program Studi Manajemen Lingkungan, 2019)
The results of this study focus on policy issues, guidelines, implementation, and expectations for Implementation of managemen environmental in order to realize environmentally friendly factory. This paper seeks to analyze the environmental impact, both in terms of benefits, as well as from environmental managemen, waste management, and evaluation & monitoring environmental report through policy analysis. Evaluation of the program used by the researchers is a Grindle evaluation model that includes the evaluation component policy and program formulation, Program Implementation, Resources alocation and Outcomes. Context Evaluation related to Environment license and AMDAL as stated in Law no. 27 of 2012. Evaluation of Policy and program formulation related to the policy AMDAL and AMDAL as guidance for environment management. Evaluation program implementation related to environment management, waste management and environmental monitoring. Resources alocation evaluation is related to facilities and infrastructure and budgeting. Outcomes evaluation is related to society complain handling, economy and social impact, This analysis tries to approach a strategy to consider: environmental management that benefits all parties, both government and society. The results of the analysis show the need for collaborative management among stakeholders (government, lokal government and lokal communities) in sustainable management of the site.